2013
DOI: 10.2337/db12-0350
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K Knockout Mitigates High-Fat Diet–Induced Cardiac Hypertrophy and Contractile Dysfunction

Abstract: The cysteine protease cathepsin K has been implicated in pathogenesis of cardiovascular disease. We hypothesized that ablation of cathepsin K protects against obesity-associated cardiac dysfunction. Wild-type mice fed a high-fat diet exhibited elevated heart weight, enlarged cardiomyocytes, increased left ventricular wall thickness, and decreased fractional shortening. All these changes were reconciled in cathepsin K knockout mice. Cathepsin K knockout partly reversed the impaired cardiomyocyte contractility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 40 publications
10
72
0
5
Order By: Relevance
“…Animal models have shown that CatK deficiency has a beneficial effect on age and obesity-related cardiac hypertrophy and atherosclerosis. [109][110][111][112][113] Currently, there are no known studies to confirm this finding in pycnodysostosis patients.…”
Section: Human Cathepsin K Deficiency and Its Phenotypesupporting
confidence: 63%
See 1 more Smart Citation
“…Animal models have shown that CatK deficiency has a beneficial effect on age and obesity-related cardiac hypertrophy and atherosclerosis. [109][110][111][112][113] Currently, there are no known studies to confirm this finding in pycnodysostosis patients.…”
Section: Human Cathepsin K Deficiency and Its Phenotypesupporting
confidence: 63%
“…[111] Furthermore, it has been shown that the ablation of this protease mitigated pressure overload-induced cardiac hypertrophy, obesity-associated cardiac hypertrophy, and contractile dysfunctions as well as prevented ageing-associated cardiac anomalies without altering cardiac fibrosis. [112,113] Little is known about the functions of CatK in the brain. The protease has been implicated in endorphin degradation and linked to schizophrenia.…”
Section: Cathepsin K Deficiency In Micementioning
confidence: 99%
“…Previous studies using CatK knockout animals provide evidence that CatK specifically mediates biological effects in cellular events 21,30 . In line with these findings, our results showed that blood flow recovery and capillary formation following hindlimb ischaemia were substantially impaired in CatK À / À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of cathepsin K alleviates both pressure overload-induced and high-fat dietinduced cardiac hypertrophy, likely through the inhibition of mammalian target of rapamycin (mTOR) and ERK pathways (13,14). On the contrary, several other cathepsins were found to be cardioprotective.…”
mentioning
confidence: 95%